HUBUNGAN PENERAPAN STANDAR PROSES PEMBELAJARAN PADA SEKOLAH MENENGAH PERTAMA DENGAN NILAI UJIAN AKHIR NASIONAL DI KABUPATEN MANOKWARI - Cipta Meliala, ; Kunto Wibowo, ; Siti Halimatus Sa’adiyah, (Pendidikan Sekolah Dasar, 2011)
Learning process in the school is composed by planning, implementation, evaluation, and control. Topic of learning consisted by introduction, topic focus, and summary as planned in the RPP was presented in the classroom. The implementation of learning process in middle high school in capital of Manokwari and its suburb region was compared to know its relation with points of national test. The information was gathered by field observation, interview, and document analysis. Learning process in middle high school in Manokwari was running and qualified as enough or good. The weakest of learning process is its implementation in the classroom. Good learning process is not always followed by a good point of national test.